Opening Doors to Independence: Why Your Child’s IEP Should Include Recreational Therapy for Leisure Skills - Archambault, MaryJo; Terpstra, Judy (PALAESTRA, 2026)
Leisure, as the pursuit of activities we choose to engage in during our free time, holds immense potential for enriching our lives. However, individuals with disabilities often face barriers that hinder their ability to participate fully in leisure activities. The delivery of leisure education to students in Special Education is of paramount importance in promoting independence and quality of life. This exploratory study investigates the delivery of leisure education to students in transition programs, aiming to understand current practices. In addition, this paper makes an argument for the inclusion of recreational therapists in the transition setting and encourages guardians to request recreational therapy as a related service on their child’s Individual Education Plan (IEP).
Keywords: dept.rec; dept.sed

Teacher and parent perspectives on extracurricular activities for students with intellectual and developmental disabilities - Cain, Irina; Bruno, Lauren; Agran, M.; Wojcik, Andrew; Achola, Edwin; Thoma, Colleen; Nixon, Cynthia; Tamura, Ronald (Inclusion, 2025)
Keywords: Extracurricular activity; Intellectual disability; Qualitative research; Semi-structured interview; dept.sed

Introduction to the special section on drivers with ASD - Volkmar, Fred (Journal of Autism and Developmental Disorders, 2025)
Keywords: Autism; Clinical psychology; Computer science; Developmental psychology; Engineering; Engineering physics; Medicine; Psychology; Public health; Section (typography); Special section; dept.sed

Considering emerging, complementary, and alternative treatments - Øien, Roald; Nordahl‐Hansen, Anders; Skarbek, Sacha; Tolkin, Samuel; Volkmar, Fred (Handbook of Evidence-Based Practices in Autism Spectrum Disorder, 2025)
Keywords: Computer science; dept.sed

Evidence-based practices in autism: where we started to where we are now - Reichow, Brian; Doehring, Peter; Volkmar, Fred (Handbook of Evidence-Based Practices in Autism Spectrum Disorder, 2025)
Keywords: Autism; Developmental psychology; Psychology; dept.sed

Evidence-based practices and treatments in autism spectrum disorder: concluding thoughts - Volkmar, Fred; Doehring, Peter; Reichow, Brian (Handbook of Evidence-Based Practices in Autism Spectrum Disorder, 2025)
Keywords: Autism; Autism spectrum disorder; Cognitive psychology; Developmental psychology; Physics; Psychology; Spectrum (functional analysis); dept.sed

AI in Special Education: Bridging Gaps, Easing Workloads, and Inspiring Inclusion - DiBattista, Eileen; Erazmus, Kelly; Tucker, Lauren (Teaching Exceptional Children, 2025)
Keywords: Bridging (networking); Inclusion (mineral); Learning disability; Special education; Teaching method; dept.sed

From Theory to Practice: A Tiered Support Model for Increasing Preservice Teachers’ Use of Behavior Specific Praise - Hynes, Kristy; Gershwin, Tracy (Journal of Educational and Psychological Consultation, 2025)
Keywords: Praise; Qualitative research; Work (physics); dept.sed

Assistive Technology Multi-Tiered System of Supports (AT-MTSS): Improving AT Delivery - McMahon, Don; Tucker, Lauren (Journal of Special Education Technology, 2025)
Keywords: Assistive technology; CLARITY; Inclusion (mineral); Psychological intervention; Special education; Special needs; Universal Design for Learning; Variety (cybernetics); accessibility; assistive technology; dept.sed; multi-tiered systems of supports; special education teacher preparation; universal design for learning

Centering Critical Engagement, Multimodal Learning, and Compassion through Language and Literacy - Mulcahy, Cara; Shaw, Louise (The Intersections of Critical Pedagogy, Critical Literacy, and Social Justice: Toward Empowerment, Equity, and Education for Liberation, 2024)
Keywords: dept.sed

Self-Monitoring to Reduce Student Distraction in Higher Education - Brahm, Meghan; Hynes, Kristy (College Teaching, 2025)
Keywords: Applied behavior analysis; Cognitive psychology; Distraction; Higher education; Mathematics education; Pedagogy; Political science; Psychology; Student engagement; classroom distraction; dept.sed; higher education; self-monitoring; student engagement

Building TRUST: Empowering Teachers to Support Students With Emotional and Behavioral Disorders - Mitchell, Carolyn; Gershwin, Tracy; Robinson, Jason; Hynes, Kristy (Intervention in School and Clinic, 2025)
Keywords: Applied psychology; Developmental psychology; Emotional and behavioral disorders; Learning disability; Mathematics education; Pedagogy; Psychology; Reading (process); Special education; dept.sed; peer-reviewed

Autism spectrum disorder in adolescents and adults: an introduction - Volkmar, Fred R.; Reichow, Brian; McPartland, James C. (Adolescents and Adults with Autism Spectrum Disorders, 2024)
Leo Kanner’s classic description of autism appeared eight decades ago. Although the pace of research has increased dramatically, research specifically focused on adolescents and adults remains limited in many respects. Numerous outcome studies have been conducted and suggest potential for markedly improved outcome with intervention. Unfortunately, studies on adults after early adulthood are sparse and, for old age, almost nonexistent, reflecting a lack of support for research in this population. This is in stark contrast to other developmental disorders in which considerable information on adult life is often available. This book summarizes work across areas, focusing on what is known and not yet known, highlighting important areas for future research. While overall outcome has improved, a small group of individuals remain in need of high levels of adult care. For all individuals, the field requires new approaches to both research and clinical service.
Keywords: Adolescents; Adults; Autism; Outcome; Supports; dept.sed

Relationships Matter: The Art of Creating Meaningful Interactions With Students - Hynes, Kristy; Gershwin, Tracy; Robinson, Jason; Mitchell, Chrissa (Beyond Behavior, 2025)
Keywords: Foundation (evidence); Mathematics education; Pedagogy; Psychological intervention; Psychology; dept.sed; peer-reviewed

Impacts of an assistive technology graduate program: a case study - Tucker, Lauren (Assistive Technology Outcomes and Benefits (ATOB), 2024)
Alumni from an Assistive Technology (AT) graduate program were invited to complete a survey and participate in focus groups to share how they are using the knowledge gained from their graduate degree and its impact on their professional careers. The sample of 27 alumni spanned seven years and a variety of professional backgrounds. This qualitative single-case study revealed impacts on careers, professional skill development, and technology skills after graduation. Participants also connected this later skill development to their concrete learning experiences within the graduate program.
Keywords: assistive technology; dept.sed; graduate program; peer-reviewed; perspectives; special education

Letter to the editor: Supporting drivers with autism and police officer interactions-Connecticut’s blue envelope program - Gleeson, M.B.; Grindle, H.; Gleeson, M.M. (Journal of Autism and Developmental Disorders, 2024)
The rising prevalence of autism spectrum disorder (ASD) has led to increased efforts to support individuals with ASD across numerous aspects of life, including driving. While obtaining a driver’s license substantially impacts quality of life and independence, it also creates distinct challenges for those with ASD. Challenges surrounding social communication, executive functioning, and sensory sensitivities are particularly evident when considering interactions between drivers with ASD and law enforcement personnel. Connecticut’s Blue Envelope Program aims to improve interactions between drivers with and ASD law enforcement by providing instructions for officers and drivers to follow during routine traffic stops on a physical, blue colored, envelope. The instructional guidelines aim to assist officers in understanding and appropriately responding to common ASD-related behaviors which may be otherwise misinterpreted and includes accommodations officers could consider during a stop. Additionally, the envelope outlines clear steps for drivers with ASD to follow through the stop as to support predictability and expectations. The widespread acceptance, efficacy and popularity of the Blue Envelope program underscores the importance of increasing awareness and understanding of ASD among law enforcement and the need for more supports to aid in these increasing interactions. Discussion is offered on a broader implementation of this program to support individuals with ASD and officers, while improving the outcomes of interactions. © The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature 2024.
Keywords: Autism; Blue envelope; Driving; Law enforcement; Police officers; dept.sed

Adapted text benefits for teachers and students: A retroactive case study - Tucker, Lauren (Journal of Learning and Teaching in Digital Age, 2021)
This case study retrospectively reflects on a self-contained teacher’s decision to pair publisher-created adapted text with audio support as part of a multicomponent reading intervention. She evolved from creating her own adapted text to implementing publisher-created adapted text throughout a school year. The study analyzed students’ reading comprehension test scores throughout the year to examine the influence of publisher-created adapted text embedded within a multi-component reading intervention. The Related-Samples Wilcoxon Signed Rank Test revealed significance (p=.043) between students’ fall and spring Reading Inventory scores, with a moderate effect size (r=.562). The teacher made the instructional decision to implement publisher-created adapted text which eliminated time consuming self-adaptation of materials (Browder et al., 2007) and her students continued to make progress with this shift of materials with some demonstrating significant progress by the end of the school year.
Number: 1
Keywords: dept.sed

Universally Designing in Universal Chaos. - Tucker, Lauren (Remote Teaching and Learning: Reflections and Practical Advice, 2021)
Looking back on a year of tumultuous teaching and learning amid restrictions set in place after the COVID-19 pandemic began in early 2020, Remote Teaching and Learning: Reflections and Practical Advice focuses not only on the trials and tribulations higher ed faculty have endured but also the insights learned, silver linings revealed, and successes achieved through emergency remote teaching. Hear from 20 educators whose contributions include: reflections on pandemic teaching; strategies and practical advice; and resources for students.Whether you’re returning to a face-to-face classroom, continuing to teach online, or exploring hybrid or HyFlex teaching, you’ll find wisdom, advice, and observations from educators with a shared commitment to student learning. Includes student handouts to use in your classroom!
Keywords: dept.sed

Whither Asperger’s post DSM-5? An opinion piece - Volkmar, F.R.; Woodbury-Smith, M. (Review Journal of Autism and Developmental Disorders, 2024)
Although first described in 1944 (the year the description of infantile autism), Asperger’s syndrome attracted little attention until the publication by Lorna Wing in early 1980. Over time, different views of the definition of Asperger’s syndrome developed. By the time of the Third Edition of the American Psychiatric Association’s Diagnostic and Statistical Manual and the Tenth Edition of the World Health Organization’s International Classification of Disease, enough information had accumulated to include the condition within the broader autism category. Asperger’s syndrome remained a focus of research interest and debate until its exclusion in the DSM-5 in 2013. We argue that the decision to remove Asperger’s syndrome 10 years ago as a distinct condition was premature. A discussion of the tensions around defining Asperger’s and concerns now arising due to the lack of this diagnostic category for new cases is provided. © 2024, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: Asperger’s disorder; Autism spectrum disorder; Autistic disorder; Classification; DSM-5; dept.sed; peer-reviewed

Culturally Responsive Special Education - Gerzel-Short, Lydia; Jerae, Kelly; Hovey, Katrina A.; Hsiao, Yun‐Ju; Wei, Yan (Advances in educational marketing, administration, and leadership book series, 2023)
Keywords: dept.sed

Preparing culturally responsive teachers: a systematic review - Miller, Rhonda D.; Gerzel-Short, Lydia; Kelly, Jerae H.; Uphold, Nicole; Hsiao, Yun-Ju; Hovey, Katrina A.; Wei, Yan (Multicultural Learning and Teaching, 2023)
As the world continues to ponder issues of equity and diversity, U.S. public schools face an expanding demographic divide between teachers and students. While diverse groups of public school students show an increase in population, the teaching workforce in the U.S. remains overwhelmingly White. The purpose of this systematic review is to examine how preservice teachers (PST) are being prepared to be culturally responsive. A total of 26 studies published between 2006 and 2020 were reviewed. The results indicate that PSTs’ learning experiences are varied and tend to be stand-alone approaches focused on changing the attitudes and beliefs of PSTs. Findings also bring to light the vagueness of terminology used in the research to define cultural groups of students, the conspicuous absence of studies related to LGBTQ+ populations, and the lack of study replications. Implications for future research are discussed.
Keywords: culturally responsive; dept.sed; diversity; peer-reviewed; pre-service teacher; teacher education; teacher preparation

Developing simulation materials to support teacher anti-racist and anti-ableist practice during iep meetings: Supporting general educator collaborative practice - Perouse-Harvey, Ebony (Advocating and Empowering Diverse Families of Students With Disabilities Through Meaningful Engagement, 2023)
Research demonstrates discriminatory and inequitable practices related to students identified with (disabilities). Inequitable practices and discrimination reveal the necessity of collaboration and advocacy as an integral part of the pedagogy of professional development for members of the IEP team. Providing pre-service (or preparing) teachers simulated experiences of individualized education program (IEP) meetings can support PSTs understanding of how ableism and racism can manifest in schools, develop skills in collaborating with families, and begin to develop advocacy practices that support students that are marginalized at the intersection of their race and ability status. This chapter focuses on how to develop materials that leverage critical theoretical frameworks, provide learning experiences that mirror teacher practice in schools, and provide authentic representations of families of color to develop PSTs collaborative and advocacy practices. © 2023 by IGI Global. All rights reserved.
Keywords: dept.sed

Increasing outcomes: principles of practice to increase writing outcomes for deaf/hard of hearing students with additional disabilities - Weir, Joan; Dostal, Hannah M. (Strategies for Promoting Independence and Literacy for Deaf Learners With Disabilities, 2023)
The ability to write clearly and effectively is an important communication skill that is necessary for school and employment, as it is often the best way to disseminate information and ideas. Both unrecorded sign and speech are ephemeral, but writing allows the author to share an experience or idea...
Keywords: dept.sed

Autism and intersectionality: Considerations for school-based practitioners - Sassu, Kari A.; Volkmar, Fred R. (Psychology in the Schools, 2022)
The purpose of this article is to explore the intersectionality of autism and sociocultural factors as well as discuss the complexities associated with appropriate assessment, diagnosis, and intervention. Based on a review of the literature, the authors present a brief history of the emergence of the term autism and highlight factors that have contributed to current concerns about failures to appropriately recognize autism within diverse populations. Referencing extant research as well as professional practice standards, this article examines aspects of autism and intersectionality, and explores some of the associated challenges related to assessment, diagnosis, and intervention. Further, the authors reflect on the critical importance of carefully considering all aspects of a child's identity when engaging in autism assessment and intervention within the school setting. School-based practitioners are provided with guidance for addressing the needs of diverse populations of students with autism.
0 citations (Crossref) [2023-10-31] _eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/pits.22757
Keywords: SES; autism; dept.csp; dept.sed; ethnicity; intersectionality; peer-reviewed; race

What are we optimizing for in autism screening? Examination of algorithmic changes in the M-CHAT - Schjølberg, Synnve; Shic, Frederick; Volkmar, Fred R.; Nordahl-Hansen, Anders; Stenberg, Nina; Torske, Tonje; Larsen, Kenneth; Riley, Katherine; Sukhodolsky, Denis G.; Leckman, James F.; Chawarska, Katarzyna; Øien, Roald A. (Autism research : official journal of the International Society for Autism Research, 2021)
The present study objectives were to examine the performance of the new M-CHAT-R algorithm to the original M-CHAT algorithm. The main purpose was to examine if the algorithmic changes increase identification of children later diagnosed with ASD, and to examine if there is a trade-off when changing algorithms. We included 54,463 screened cases from the Norwegian Mother and Child Cohort Study. Children were screened using the 23 items of the M-CHAT at 18 months. Further, the performance of the M-CHAT-R algorithm was compared to the M-CHAT algorithm on the 23-items. In total, 337 individuals were later diagnosed with ASD. Using M-CHAT-R algorithm decreased the number of correctly identified ASD children by 12 compared to M-CHAT, with no children with ASD screening negative on the M-CHAT criteria subsequently screening positive utilizing the M-CHAT-R algorithm. A nonparametric McNemar's test determined a statistically significant difference in identifying ASD utilizing the M-CHAT-R algorithm. The present study examined the application of 20-item MCHAT-R scoring criterion to the 23-item MCHAT. We found that this resulted in decreased sensitivity and increased specificity for identifying children with ASD, which is a trade-off that needs further investigation in terms of cost-effectiveness. However, further research is needed to optimize screening for ASD in the early developmental period to increase identification of false negatives. © 2021 The Authors. Autism Research published by International Society for Autism Research and Wiley Periodicals LLC.
4 citations (Crossref) [2023-10-31] https://pubmed.ncbi.nlm.nih.gov/34837355/
Keywords: Article; Autism Spectrum Disorder; Autistic Disorder; Checklist; Child; Cohort Studies; Female; Humans; Infant; M CHAT R algorithm; M CHAT algorithm; Mass Screening; McNemar test; Mothers; algorithm; autism; checklist; child; cohort analysis; controlled study; cost effectiveness analysis; dept.sed; developmental stage; diagnostic accuracy; diagnostic test accuracy study; early diagnosis; false negative result; female; gold standard; human; infant; major clinical study; mass screening; mother; nonparametric test; peer-reviewed; procedures; process optimization; psychometry; reference value; scoring system; sensitivity and specificity; statistical significance

Partnering to create a core communication board to improve theater experiences - Tucker, Lauren (Assistive Technology Outcomes and Benefits, 2021)
This article outlines a partnership between a nonprofit theater in Connecticut and pre-service special education teachers at a local university. The goal of the collaboration was to increase the accessibility of the sensory-friendly performances and events designed for students in PK-12. The process of creating visual supports and a core communication board is shared, in addition to the designing of training and implementation phases. The project not only resulted in improved supports for the school-aged sensory-friendly events for the next season, but also in a demonstrable perspective shift on the importance of inclusivity and community communication supports among pre-service teachers and community members. © 2021, Assistive Technology Industry Association. All rights reserved.
Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85114899160
Keywords: dept.sed; peer-reviewed; ⛔ No DOI found

Initial support for a behavioral skills training package with computer-based instruction to teach conversation skills to adults with autism spectrum disorders, with an assessment of socially meaningful behavior change1 - Groskreutz, Nicole C.; Groskreutz, Mark P. (Evidence-Based Communication Assessment and Intervention, 2021)
0 citations (Crossref) [2023-10-31]
Keywords: Article; Asperger syndrome; adolescent; adult; autism; behavior change; behavior therapy; clinical article; communication skill; computer aided design; conversation; dept.sed; follow up; human; parental attitude; patient attitude; peer-reviewed; skill; social validity

Transfer of writing skills across genres among deaf and hard of hearing elementary writers - Dostal, Hannah M.; Wolbers, Kimberly A.; Weir, Joan (International Journal of Educational Research, 2021)
Thirty-seven deaf and hard of hearing (DHH) students in grades four through six participated in a year of Strategic and Interactive Writing Instruction, an approach to writing instruction designed to be responsive to DHH students’ unique language experiences and profiles. The current study investigated the transfer of writing skills between genres by analyzing participants’ recount, information report, and persuasive writing samples at four time points: at the beginning of the academic year, immediately before genre-focused instruction, at the end of 9 weeks of instruction in a genre, and 9 weeks after the conclusion of instruction in a genre. Results from the study demonstrate that DHH students transfer genre-specific writing skills between genres. © 2021 The Authors
4 citations (Crossref) [2023-10-31]
Keywords: dept.sed; peer-reviewed

Preparing educators for inclusive bilingual education: A boundary crossing laboratory between professional groups - Martínez-Álvarez, P; López-Velásquez, A; Kajamaa, A (Cultural-Historical Psychology, 2021)
Teacher education programs prepare candidates for bilingual, English as a second language, or special education as separate professionals. This creates challenges when teaching bilingual children with disabilities. There is a need to cross boundaries combining expertise and preparing teachers for children's uniqueness. Responding to this need, the researchers organized a change laboratory with 14 professors and two State Department of Education consultants. The study explored boundary expressions and their relationship to the larger activity. It also looked at the learning that took place during boundary crossing efforts. Boundaries were identified around bilingual teacher preparation, cross-disciplinary programmatic, and paradigmatic aspects. While boundary crossing at the intrapersonal level and at the interpersonal level were important, the need to engage multiple institutions was centered. In addition, the discussion manifested that for inclusive bilingual education teacher preparation, there was a need to go beyond the institutional level to reach to policy makers and address the sociopolitical resistance against bilingual education. Throughout the study, participants engaged primarily in the epistemic learning actions of analyzing and modeling. Through volitional actions, the participants realized a renewed object for their activity. This study widens the understanding of possibilities for taking shared educational responsibility through boundary crossing between professionals in preparation programs. © 2021. All Rights Reserved.
1 citations (Crossref) [2023-10-31]
Keywords: dept.sed; peer-reviewed

The Diagnosis of Autism: From Kanner to DSM-III to DSM-5 and Beyond - Rosen, Nicole E.; Lord, Catherine; Volkmar, Fred R. (Journal of Autism and Developmental Disorders, 2021)
In this paper we review the impact of DSM-III and its successors on the field of autism—both in terms of clinical work and research. We summarize the events leading up to the inclusion of autism as a “new” official diagnostic category in DSM-III, the subsequent revisions of the DSM, and the impact of the official recognition of autism on research. We discuss the uses of categorical vs. dimensional approaches and the continuing tensions around broad vs. narrow views of autism. We also note some areas of current controversy and directions for the future.
Keywords: Article; Asperger syndrome; Autism; Autism Spectrum Disorder; Autistic Disorder; Categorical; DSM; DSM-5; DSM-III; DSM-IV; Diagnostic and Statistical Manual of Mental Disorders; Dimensional; History; Humans; ICD-10; ICD-11; Psychology; Recognition; autism; clinical feature; clinical research; cognition; cultural factor; dept.sed; dept.swk; developing country; echolalia; ethnic group; human; language ability; medical history; peer-reviewed; pervasive developmental disorder not otherwise specified; psychiatric diagnosis; psychological aspect; race; sex difference; social class; symptom; tension

Literacy development at camp: Leveraging language models - Dostal, Hannah M.; Scott, Jessica A.; Weir, Joan; Kang, Ki Y.; Amadi-Ihebuzor, Chidinma; Bernard, Teri-Ann (Reading Teacher, 2021)
There is little research on effective educational experiences for deaf and hard-of-hearing (d/hh) children in Jamaica. Using a formative and design experiment framework, in this project we explored the potential efficacy of an intensive literacy camp that provided professional development for d/hh adults working in classrooms with d/hh children, and provided literacy instruction for elementary-age campers. We found that the children improved in all tested areas, and observations of d/hh adults provided evidence that with minimal training they were able to implement important facets of literacy instruction with the campers. Further research on these types of experiences and their potential for lasting impact after the camp is necessary. © 2021 International Literacy Association
1 citations (Crossref) [2023-10-31] Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85102715654
Keywords: dept.sed; peer-reviewed

Student perception on the impact of the Livescribe smartpen as an accommodation - Tucker, Lauren; Zamfir, Bogdan (Universal Access in the Information Society, 2021)
The goal of this exploratory qualitative study was to determine how students with disabilities in higher education are using the Livescribe smartpen in their note-taking process and the perceived impact on their academic tasks. Based on participant interviews, many are using the Livescribe smartpen for recording class lectures while taking notes and for engaging with the content outside of the class session. All but one participant reported a perceived positive impact from the use of the Livescribe pen. The positive impacts included improved focus, higher academic outcomes, independence, and capturing complete notes. One unexpected trend that was revealed is that the majority of the participants adjusted their use of the Livescribe smartpen accommodation based on the professor’s teaching style and course structure. © 2021, The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature.
1 citations (Crossref) [2023-10-31] Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85103414669
Keywords: Course structure; Higher education; Information science; Information systems; Note taking; Qualitative study; Software engineering; Student perceptions; Teaching styles; dept.sed; peer-reviewed

Seeing the forest and the trees: Disentangling autism phenotypes in the age of DSM-5 - Volkmar, Fred R.; Woodbury-Smith, Marc; Øien, Roald A. (Development and Psychopathology, 2021)
This paper, written in honor of Professor Ed Zigler, focuses on some of the themes in developmental disabilities research that were so central to his work. It has now been nearly 80 years since Leo Kanner first identified the prototypic form – early infantile autism – of what is now autism spectrum disorder. In this article we summarize the development of the concept and the important accumulation of knowledge over time that has now led us to the recognition of a broader autism phenotype just as, at the same time, the current official diagnostic system in the USA has narrowed the concept. We also address current controversies regarding autism as the diagnosis is impacted by age and developmental factors, gender, and cultural issues. In parallel to the work on intellectual deficiency and development pioneered by Zigler and his colleagues, we summarize some of the challenges for the years ahead.
8 citations (Crossref) [2023-10-31] Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85102496361
Keywords: Autism Spectrum Disorder; Autistic Disorder; Diagnostic and Statistical Manual of Mental Disorders; Humans; Phenotype; Psychology; Recognition; autism; dept.sed; human; peer-reviewed; phenotype

P. Thomas: I See Things Differently: A First Look at Autism - Kuvish (Journal of Autism and Developmental Disorders, 2020)
0 citations (Crossref) [2023-10-31]
Keywords: dept.sed

Motivating students with learning disabilities to read - Wei, Yan; Spear-Swerling, Louise; Mercurio, Mia (Intervention in School and Clinic, 2021)
Students may lack the motivation to read for many reasons, including inadequate access to interesting texts, limited encouragement to read for pleasure from adults, instructional practices that do not foster engagement in learning, or a history of reading failure. This article focuses on students with reading disabilities who may have a long-standing dislike of reading born of repeated negative experiences with learning to read. Motivating these students to read for pleasure may seem like an unattainable goal. However, past difficulties in reading do not necessarily mean that children will dislike reading forever. In conjunction with appropriate academic interventions, student interest in reading might be improved by motivational interventions aligned with a theoretical framework discussed in this article: (a) choosing interesting texts to read, (b) stimulating knowledge-based interest, and (c) enhancing task-based interest.
2 citations (Crossref) [2023-10-31] Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85086673210
Keywords: dept.sed; peer-reviewed

The print exposure of teacher candidates in relation to their achievement and self-ratings of early reading experiences - Spear-Swerling, Louise; Wei, Yan; Dostal, Hannah; Hernandez, Brittney (Reading and Writing, 2020)
This study examined the print exposure of teacher candidates (N = 195) in relation to their GPAs, achievement in reading and writing on the SAT, and their self-ratings of their own early (K to Grade 5) reading experiences. Participants came from undergraduate and Masters programs in varied certification areas and from two different universities. Print exposure measures included author recognition tests for both fiction and nonfiction; a questionnaire about participants’ current voluntary reading habits for books, magazines, newspapers, and digital print media; and favorite authors/books questions. Exploratory factor analysis suggested four factors underlying the different print exposure measures: (1) fiction book reading volume; (2) current magazine and newspaper reading; (3) nonfiction book reading volume and (4) current book reading habits for enjoyment. Only fiction and nonfiction book reading volume related positively to participants’ achievement, in writing as well as reading, and to their early reading experience ratings. A subgroup of participants who had taken a specific reading methods course involving structured language content, and who had positive early reading experience self-ratings, had higher performance in the course than did participants with mixed or negative self-ratings, although the two groups did not differ in overall GPA. Findings support the view that different measures of print exposure tap somewhat different aspects of print exposure, with differing relationships to varied indicators of achievement. Results also support concerns about the reading volume and print exposure of some teacher candidates. © 2020, Springer Nature B.V.
2 citations (Crossref) [2023-10-31] WOS:000563131900009
Keywords: Print exposure; Reading; Reading habits; Teacher candidates; Teacher preparation; Writing; dept.sed; peer-reviewed

Transdisciplinary Approach Practicum for Speech-Language Pathology and Special Education Graduate Students - Weiss, Deborah; Cook, Barbara; Eren, Ruth (Journal of Autism and Developmental Disorders, 2020)
Speech-language pathology and special education graduate student teams participated in an intensive summer practicum for social communication skills with children with autism spectrum disorders, utilizing a transdisciplinary approach that aligned to the frameworks utilized for implementation science. Questionnaires measuring transdisciplinary approach knowledge and comfort level were administered pre/post-practicum. Results of the questionnaires, written daily team reflections, course evaluations, and a focus group interview indicated an increase in all measures, including an increased knowledge of TA, increased understanding and comfort level with the other discipline, and a higher level of confidence and openness in working collaboratively utilizing a transdisciplinary approach. © 2020, Springer Science+Business Media, LLC, part of Springer Nature.
12 citations (Crossref) [2023-10-31] WOS:000516272800002
Keywords: Academic Performance; Article; Autism Spectrum Disorder; Autism spectrum disorder; Child; Collaborative teaming; Communication; Education; Special; Female; Humans; Implementation science; Interdisciplinary Research; Interprofessional collaboration; Male; Special education; Speech-Language Pathology; Speech-language pathology; Students; Health Occupations; Surveys and Questionnaires; Transdisciplinary; academic achievement; autism; child; comfort; communication skill; course evaluation; dept.cmd; dept.sed; education; female; graduate student; health student; human; implementation science; interdisciplinary education; interdisciplinary research; interpersonal communication; interview; knowledge; male; peer-reviewed; pretest posttest design; priority journal; procedures; professional development; psychology; quantitative analysis; questionnaire; social competence; special education; speech disorder; teacher; training

Core dimensions of autism spectrum disorders - Volkmar, Fred R.; Jackson, Scott L.J. (New Oxford Textbook of Psychiatry, 2020)
Autism spectrum disorder (ASD) is a neurodevelopmental disorder that manifests during the early developmental period of childhood. Behaviourally characterized by impairments in social interaction and communication, in combination with stereotyped and restricted patterns of behaviour and/or interest, it is currently believed that ASD occurs in approximately 1–2% of individuals. ASD is more prevalent among males than females (4–5:1), but the mechanisms resulting in this discrepancy are still unclear. This chapter will serve as an introduction to ASD, covering the topics of disorder history, prevalence rates, demographics, diagnostic criteria, differential diagnosis, and discussions on current and future diagnostic classification systems. The remaining chapters within Section 4 will then provide detailed discussions on more specific topics related to ASD, including current understandings of treatment planning, prevention and epidemiology, genetics, imaging, and disorder management.
tex.ids: volkmarCoreDimensionsAutism2020a
Keywords: dept.sed

School Leadership for Learning: Learning Theory to Improve Professional Practice - Gregory, Jess L.; Ben-Avie, Michael; Billups, Felice; Grassetti, Mary; Hesser, Tiffany; Lawlor, Jennifer Lynne; Martone, Drey; Maykel, Cheryl; Minkos, Marlena L.; Paslov, Linda; Trombly, Christopher; Tucker, Lauren; et al. (Jess L. Gregory, 2021)
Keywords: Educational leadership; School administrators; Handbooks; manuals; etc; In-service training; School administrators; In-service training; Teachers; dept.edl; dept.sed; faculty_collection